Contiguous and Atomically Thin Pt Film with Supra‐Bulk Behavior Through Graphene‐Imposed Epitaxy. (18th September 2019) - Choi, Ji Il; Abdelhafiz, Ali; Buntin, Parker; Vitale, Adam; Robertson, Alex W.; Warner, Jamie; Jang, Seung Soon; Alamgir, Faisal M.
Abstract: The nature of the atomic configuration and the bonding within epitaxial Pt‐graphene films is investigated. Graphene‐templated monolayer/few‐multilayers of Pt, synthesized as contiguous 2D films by room temperature electrochemical methods, is shown to exhibit a stable 100 structure in the 1–2 layer range. The fundamental question being investigated is whether surface Pt atoms rendered in these 2D architectures are as stable as those of their bulk Pt counterparts. Unsurprisingly, a single layer Pt on the graphene (Pt_1ML/GR) shows much larger Pt dissociation energy (−7.51 eV) than does an isolated Pt atom on graphene. However, the dissociation energy from Pt_1ML/GR is similar to that of bulk Pt(100), −7.77 eV, while in bi‐layer Pt on the graphene (Pt_2ML/GR), this energy changes to −8.63 eV, surpassing its bulk counterpart. At Pt_2ML/GR, the dissociation energy also slightly surpasses that of bulk Pt(111). Bulk‐like stability of atomically thin Pt–graphene results from a combination of interplanar PtC covalent bonding and inter/intraplanar metallic bonding. This unprecedented stability is also accompanied by a metal‐like presence of electronic states at the Fermi level. Such atomically thin metal‐graphene architectures can be a new stable platform for synthesizing 2D metallic films with various applications in catalysis, sensing, and electronics. Abstract : Graphene‐templated monolayer to few‐multilayers of Pt, synthesized as contiguous 2D films by room temperature electrochemical methods, exhibits a 100 structure where the surface Pt atoms are more stable than their bulk Pt 100 or Pt 111 counterparts. This supra‐bulk stability of the 2D Pt/graphene results from a combination of inter‐planar PtC covalent bonding and inter/intraplanar metallic bonding.